Usability Testing of an Interactive Communication Tool to Help Children Express Their Cancer Symptoms. (September 2018) - Tsimicalis, Argerie; Rennick, Janet; Stinson, Jennifer; May, Sylvie Le; Louli, Julie; Choquette, Anne; Treherne, Stephanie; Berube, Sarah; Yoon, Sunmoo; Ruland, Cornelia
Objective: Sisom is an interactive computer software program that allows children to rate the severity of their cancer symptoms. The study objectives were to describe the usability of Sisom in terms of ease of use, usefulness, and aesthetics and to offer suggestions for improvement.Method: A multisite, descriptive study was conducted to describe the usability of Sisom. A purposive sample of children, ages 6 to 12 years, being treated for cancer was recruited. English- and French-speaking children completed the eight tasks in Sisom recorded using Morae software and provided input via an audiotaped interview. Data were downloaded, transcribed verbatim, and analyzed descriptively.Results: Thirty-four children with varying cancers participated. The majority of children liked Sisom and found Sisom easy to use, found it to be helpful in expressing their symptoms, and were satisfied with the aesthetics. Some children provided suggestions for improvement to optimize Sisom use in Canada.Conclusions: Children's positive responses and desire to use Sisom again suggest that future research should be directed toward implementing and evaluating its effectiveness in a variety of settings.